INTRALINGUAL UNDERSTANDING OF POPULAR SCIENTIFIC WORDS ABOUT SHARIA ECONOMICS - Faridy, Najihatul; Lubis, Nurliza; Bania, Allif Syahputra (STKIP Persada Khatulistiwa Sintang, 2023)
The terms that arise regarding the Sharia economy are common in the community, especially in Aceh Province where this area is known as the Veranda of Mecca city. With the rapid development of Sharia understanding, a qualified understanding is needed by the community regarding terms related to the Islamic economy. The solution that can be offered is strengthening community understanding regarding the intralingual translation of Sharia terms. This research wasÂ a descriptive-qualitative research. The data was compiled from test results in the form of intralingual translation regarding 10 sharia terms to 91 purposive selected early semester students of the economics faculty from May 15 to June 12 in 2023 at Samudra University which was carried out online with the help of Google forms and distributed via the WhatsApp application. The research data that had been analyzed will be translated which could be classified as a good translation or not. The results of the research that obtained the majority of correct answer ranges regarding the understanding of Sharia terms. This underlies that the term sharia for students in Aceh is well understood so that the development of the sharia system can be in harmony with the insights of the people